Contract Formation in an Internet Age - Rawls, Amelia (Science and Technology Law Review, 2009)
Should the “mailbox” doctrine of contract acceptances be applied in technological contexts far beyond the nineteenth century context for which it was established? Among modern contracting parties, the e-mail inbox has largely replaced the postal mailbox and the near-instantaneous process of electronic communication can mimic the characteristics of a face-to-face discussion. Such technological advancements of the late-twentieth and twenty-first centuries pose a challenge to the doctrinal and normative rationales articulated by the Adams v. Lindsell court and other early “mailbox” rule advocates. Moreover, the advent of electronic communication has implications even for application of the ―”mailbox” precedent within the framework of postal and other traditional communication systems. Only a receipt-based contracting precedent, applied to technologies both new and old, can properly enhance inter-jurisdictional legal uniformity and incentivize efficient contracting behavior.